\(2x=3y\)=> \(\frac{x}{3}=\frac{y}{2}\)
Áp dụng tính chất dãy tỉ số bằng nhau ta có :
\(\frac{x}{3}=\frac{y}{2}=\frac{x+y}{3+2}=\frac{10}{5}=2\)
=> \(\hept{\begin{cases}\frac{x}{3}=2\\\frac{y}{2}=2\end{cases}}\)=> \(\hept{\begin{cases}x=6\\y=4\end{cases}}\)
\(3x=4y\)=> \(\frac{x}{4}=\frac{y}{3}\)=> \(\frac{2x}{8}=\frac{3y}{9}\)
Áp dụng tính chất dãy tỉ số bằng nhau ta có :
\(\frac{2x}{8}=\frac{3y}{9}=\frac{2x+3y}{8+9}=\frac{34}{17}=2\)
=> \(\hept{\begin{cases}\frac{x}{4}=2\\\frac{y}{3}=2\end{cases}}\)=> \(\hept{\begin{cases}x=8\\y=6\end{cases}}\)
\(x:2=y:(-5)\)=> \(\frac{x}{2}=\frac{y}{-5}\)
Áp dụng tính chất dãy tỉ số bằng nhau ta có :
\(\frac{x}{2}=\frac{y}{-5}=\frac{x-y}{2-\left[-5\right]}=\frac{7}{7}=1\)
=> \(\hept{\begin{cases}\frac{x}{2}=1\\\frac{y}{-5}=1\end{cases}}\)=> \(\hept{\begin{cases}x=2\\y=-5\end{cases}}\)